2016
DOI: 10.1016/j.cell.2015.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Actin Dynamics Regulates Dendritic Cell-Mediated Transfer of HIV-1 to T Cells

Abstract: SUMMARY Whereas human dendritic cells (DCs) are largely resistant to productive infection with HIV-1, they have a unique ability to take up the virus and transmit it efficiently to T lymphocytes through a process of trans-infection or trans-enhancement. To elucidate the molecular and cell biological mechanism for trans-enhancement, we performed an shRNA screen of several hundred genes involved in organelle and membrane trafficking in immature human monocyte-derived dendritic cells (MDDCs). We identified TSPAN7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 54 publications
(80 reference statements)
6
83
0
1
Order By: Relevance
“…This analysis revealed significant enrichment of, among others, genes involved in focal adhesion (Figure 1E). Among these were CFL1, a protein that depolymerizes F-actin and that, upon knockdown, was shown to enhance transinfection of HIV-1 between dendritic cells (DCs) and T lymphocytes (Ménager and Littman, 2016); CD99, which is involved in T cell adhesion and leukocyte migration (Bernard et al, 2000; Hahn et al, 1997; Sohn et al, 2001); and ATP1B1, which is a subunit of the Na + /K + transporter. These results suggest that Vpu-mediated immune evasion strategies may affect a broader range of host cell functions than previously appreciated, including host metabolic processes and plasma membrane activities.…”
Section: Resultsmentioning
confidence: 99%
“…This analysis revealed significant enrichment of, among others, genes involved in focal adhesion (Figure 1E). Among these were CFL1, a protein that depolymerizes F-actin and that, upon knockdown, was shown to enhance transinfection of HIV-1 between dendritic cells (DCs) and T lymphocytes (Ménager and Littman, 2016); CD99, which is involved in T cell adhesion and leukocyte migration (Bernard et al, 2000; Hahn et al, 1997; Sohn et al, 2001); and ATP1B1, which is a subunit of the Na + /K + transporter. These results suggest that Vpu-mediated immune evasion strategies may affect a broader range of host cell functions than previously appreciated, including host metabolic processes and plasma membrane activities.…”
Section: Resultsmentioning
confidence: 99%
“…We suspect that this controversy in the field debating whether or not HIV-1 gets inside the cell through endocytosis (Marin and Melikyan, 2015) has deviated the attention from the actual role of DNM2 during HIV-1 fusion. Nevertheless, there is growing interest in the field to understand the role of actin dynamics in HIV infection: a recent report (Ménager and Littman, 2016) points at the importance of DNM2 in dendritic cells mediated trans-enhancement of CD4 T cell infection by HIV in vitro. In this scenario, insights about the true role of DNM2 during single virus fusion are needed to fully understand the mechanisms taking place (Padilla-Parra and Dustin, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have also shown that DC-SIGN mediated internalized HIV-1 particles undergo degradation and subsequent presentation of HIV-1 antigen to T-cells535455. Recent research indicates that surface-bound HIV-1 on DCs is more effectively transmitted to T-cells, rather than the internalized HIV-1 particle3137565758.…”
Section: Discussionmentioning
confidence: 99%